Length-weight relationships and condition factors of Mormyridae (Teleostei: Osteglossiformes) from Niger River at Northern Benin: Needs for ecosystem restoration and species management - ADJIBADE, Nambil Kayodé; Adite, Alphonse; ARAME, Hamidou; SIDI IMOROU, Rachad; Sonon, Stanislas Pejanos (My University, 2019)
Length-weight patterns and condition factors of eleven (11) Mormyrid fishes have been examined in Niger River in Northern Benin to evaluate the plumpness of the fishes in this riverine habitat. Fishing gears such as gill net, cast net and seine have been used for monthly samplings and a total of 6825 Mormyrid individuals has been collected from February 2015 to July 2016. Mormyrid abundance varied from 09 individuals for Mormyrus hasselquisti to 2,985 for Marcusenius senegalensis. The size structure showed unimodal standard length distribution for eight (8) species and revealed that juveniles were mostly exploited. Length-weight models displayed allometric coefficients (b) varying between 2.2469 and 3.632 indicating positive and negative allometric growth with determination coefficients (r2) ranging between 0.71 and 0.99. Condition factor varied with habitats and seasons and the highest K=4.94 was recorded for Brienomyrus niger and the lowest K=0.42 was recorded for the dominant species, Marcusenius senegalensis. These data constitute valuable fisheries documentation that will contribute to Mormyrids management and conservation in order to assure a sustainable exploitation of elephant fishes in Niger River.
Keywords: Length-weight models; Condition factor; Conservation/Fisheries; Mormyrids; Niger River